Scientific legacy of L. P. Shilnikov: to the 90th anniversary - Gonchenko, Sergey Vladimirovich; Malkin, Andrej Mihajlovich (Известия высших учебных заведений: Прикладная нелинейная динамика)
This year we celebrate the 90th anniversary of Leonid Pavlovich Shilnikov (1934-2011), an outstanding Russian mathematician and one of the founders of the mathematical theory of dynamic chaos and the theory of global bifurcations of multidimensional systems.